Clinical and Imaging Prognosis in Patients with Delayed Encephalopathy after Acute Carbon Monoxide Poisoning - Jinzhi Liu; Zhihua Si; Jie Liu; Yan Lin; Jing Yuan; Shan Xu; Yan He; Tao Zhang; Aihua Wang (Behavioural Neurology)
Objective. To study the clinical manifestations, magnetic resonance imaging (MRI) findings, and prognosis of delayed encephalopathy after carbon monoxide poisoning (DEACMP). Methods. The medical records of 20 patients with DEACMP were retrospectively reviewed. All the patients received hyperbaric oxygen treatment and other treatments as necessary. Results. The patients had diverse clinical manifestations, including memory deficits, personality changes, cognitive or executive function deficits, mood disorders, Parkinsonism, dystonia or other motor impairments, and akinetic mutism. MRI revealed lesions in the bilateral cerebral white matter and/or basal ganglia. Except for the pathologically confirmed DEACMP, epileptic seizure, hemiplegia, and vegetative state, the remaining symptoms had been improved, especially the cognitive impairment, which had been decreased from 95% to 25% and psychiatric symptoms also decreased from 95% to 55% at the 6-month follow-up. Conclusions. The prognosis of patients with DEACMP was poor, and they had a relatively severe disability. The early use of hyperbaric oxygen is of great significance to improve clinical efficacy and get a better prognosis.